Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2003
DOI: 10.1046/j.1471-8286.2003.00440.x
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphic microsatellites in white rhinoceros

Abstract: The southern white rhinoceros (Ceratotherium simum simum) has suffered severe reductions in population size over the last 150 years as a result of overhunting. We optimized 10 southern white rhinoceros microsatellite loci and tested them on 30 individuals from the largest remaining population of this species. Five of the 10 loci were polymorphic with mean expected heterozygosity of 0.578, mean polymorphic information content of 0.481 and mean number of alleles 2.8. Although these data suggest low genetic varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
15
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 9 publications
(9 reference statements)
3
15
1
Order By: Relevance
“…It is apparent that low levels of genetic diversity characterize southern white rhinoceros populations, and the results from our study are consistent with other microsatellite studies in this species (Seror et al 2002;Florescu et al 2003;Nielsen et al 2008 To date, our study population has produced just one inbred F 2 individual from seven offspring in the F 2 cohort. While many species demonstrate deleterious effects from inbreeding depression (Frankham et al 2002), in both managed and natural populations of free-ranging, long-lived species these effects are very difficult to measure.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…It is apparent that low levels of genetic diversity characterize southern white rhinoceros populations, and the results from our study are consistent with other microsatellite studies in this species (Seror et al 2002;Florescu et al 2003;Nielsen et al 2008 To date, our study population has produced just one inbred F 2 individual from seven offspring in the F 2 cohort. While many species demonstrate deleterious effects from inbreeding depression (Frankham et al 2002), in both managed and natural populations of free-ranging, long-lived species these effects are very difficult to measure.…”
Section: Discussionsupporting
confidence: 91%
“…Loci were selected based on data from Coutts (2009) and included 7B and 7C (Florescu et al 2003), WR1 and WR2 (reported in Nielsen et al 2008, redesigned from loci reported in Florescu et al 2003), BR6 (Cunningham et al 1999), DB1, DB44 and DB49 (Brown and Houlden 1999) and Rh7, Rh8 and Rh9 (Zschokke et al 2003). PCR conditions followed Coutts (2009) and Menotti-Raymond et al (2005) and cycle conditions were 5 adapted where needed (see Online Resource S2 for details).…”
Section: Dna Extraction and Microsatellite Genotypingmentioning
confidence: 99%
“…The black rhinoceros (Diceros bicornis) is one of the most endangered species in Africa, with population estimates ranging from 3,600 to 2,400 individuals remaining (International Rhino Foundation 2006), and the white rhinoceros (Ceratotherium simum), is estimated to have a remaining population size around 11,000 individuals (International Rhino Foundation 2006). The establishment of a genetic diversity database within these species will help conservation efforts with regards to translocation of individuals, population viability assessments that are in the best interest of the rhinoceroses (Harley et al 2005;Florescu et al 2003) and will help decisions in the future with regards to increasing or decreasing genetic diversity of the rhinoceroses. Overall this will help conservation managers make critical decisions that will ultimately lessen the species' risk for extinction.…”
mentioning
confidence: 99%
“…Microsatellite primer sets were obtained from GenBank sequences and published papers for both the black and white rhinoceros (Florescu et al 2003;Brown and Houlden 1999). Only one (AY138544) of the five primers for white rhinoceroses published by Florescu et al (2003) could be confirmed from the sequences available on GenBank.…”
mentioning
confidence: 99%
“…Twelve microsatellite loci: BR4, BR6, BR17 (Cunningham et al 1999), DB1, DB14, DB23, DB44 (Brown and Houlden 1999), RHI32A (Florescu et al 2003), SW35 (Rohrer et al 1994), AF129734 (Nielsen et al 2008) B1RH37D and B1RH2B (QUMEL, unpublished) were used (see Table S1 for primer sequences and multiplex conditions). The PCR optimization for each locus was as follows: 2 ng of template DNA, 1.5-2.5 mM MgCl 2 , 2 mM dNTP's, 1 lM forward and 1 lM reverse primer, 0.10 U Taq DNA polymerase and ddH 2 O to a final volume of 15 ll.…”
Section: Samplesmentioning
confidence: 99%